GERM-22. DECISION-MAKING MANAGEMENT GUIDELINE FOR CHILDREN AND YOUNG PEOPLE UP TO 19 YEARS (CYP) PRESENTING WITH IDIOPATHIC PITUITARY STALK THICKENING (iTPS) AND/OR IDIOPATHIC CENTRAL DIABETES INSIPIDUS (iCDI). Issue 2 (22nd June 2018) - Cerbone, Manuela; Visser, Johannes; Bulwer, Chloe; Ederies, Ashraf; Vallabhaneni, Kirtana; Ball, Stephen; Kamaly, Ian; Grossman, Ashley; Gleeson, Helena; Korbonits, Marta; Nanduri, Vasanta; Tziaferi, Vaya; et al.
Abstract: AIM: To develop a high-quality national guideline for the assessment and management of CYP presenting with iTPS and/or iCDI before their 19th birthday, as a joint endeavour by the Britsh paediatric endocrine and oncology societies (BSPED/CCLG) and meeting approved commissioning standards (RCPCH/NIHCE). METHODS: The interdisciplinary guideline development group (GDG) identified 64 clinical questions. These were reviewed by stakeholders and used to direct a systematic literature search (January 1990 - March 2017). 568 articles were appraised using the GRADE system. Where there was sufficient evidence, the GDG made a guideline recommendation. Where high quality evidence was lacking, the GDG drafted recommendations based on their expert opinion and reviewed these using two rounds of Delphi consensus with international experts. RESULTS: In 11 case series (741 paediatric patients) the commonest individual causes of TPS/CDI were Langerhans cell hystiocytosis (16%), germ cell tumours (13%) and craniopharingiomas (12%). A range of congenital defects accounted for 19% of cases. Infectious diseases (2%), trauma (1%) and inflammatory/autoimmune conditions (1%) were rare. Twenty-nine percent remained idiopathic and some causes of TPS in adults (metastatic tumours and neurosarcoidosis) were not reported in children. The definition of TPS was not consistent across studies. A guideline and decision-making flowchart were developed. CONCLUSION: The likely aetiology of TPS/CDI in children differs from that in adults and justifies the development of age-appropriate management guidelines. This will form the basis of future audits of practice and outcomes and is intended to improve the care and service provision to CYP with apparent idiopathic TPS/CDI.